Fast computation method of static voltage stability using geometric parameter adjustment for the continuation power flow. Issue 2 (10th November 2020) - Kuroda, Eisuke; Watanabe, Masahiro; Kato, Daichi; Saito, Nao; Yatsu, Masahiro
Abstract: This paper presents a fast computation method of static voltage stability using geometric parameter adjustment for the continuation power flow. The conventional method has the following problems: voltage stability assessment (VSA) is high accuracy but there is much total convergence calculation number of times. The features of the proposed method are following: (1) to change the step size of a geometric parameter in prediction part, (2) to adjust a geometric parameter using temporary maximum loading point (MLP) by Look‐Ahead method. The proposed method has an advantage of being able to maintain high accuracy for VSA and to calculate less total convergence calculation number of times than conventional methods in IEEE test case of 118 and 300 bus systems.